Fluoroscopic-guided hysteroscopic tubal cannulation results in high technical success and pregnancy rates comparable with the more traditional laparoscopically guided hysteroscopic tubal cannulation - Martin Keltz, M.D; Sarah C. Rubin, B.S; Emma Brown, B.A; Moses Bibi, B.S; May-Tal Sau (Elsevier, 2024)
Objective: To compare women with proximal tubal obstruction (PTO) undergoing hysteroscopic tubal cannulation with fluoroscopic guidance vs. laparoscopic guidance. Design: Retrospective cohort study. Setting: All fluoroscopically-guided hysteroscopic tubal cannulations were performed in an ambulatory suite. All laparoscopically-guided hysteroscopic tubal cannulations were performed in a hospital operating room. Patients: Infertile women with unilateral or bilateral PTO on hysterosalpingography who failed selective salpingography in the radiology suite and had a planned laparoscopy or hysteroscopy in the operating room for defects seen on sonohysterography were studied. Intervention: All women had a Novy catheter system positioned hysteroscopically to cannulate the occluded fallopian tube(s). Women undergoing fluoroscopically guided hysteroscopic tubal cannulation (FHTC), which used contrast and C-arm pelvic imaging at an ambulatory center, were compared with those undergoing hospital-based laparoscopically guided hysteroscopic tubal cannulation (LHTC) with laparoscopic visualization. Main Outcome Measurements: Tubal cannulation success; bilateral cannulation success; tubal perforations; post-FHTC non-in vitro fertilization (non-IVF) intrauterine pregnancies; days from procedure to pregnancy for non-IVF intrauterine pregnancies; and time to non-IVF pregnancy hazards ratio. Results: A total of 76 infertile women undergoing either FHTC (34 women) or LHTC (42 women) between 2015 and 2019 were included. Demographic variables were similar among the 2 groups. A total of 31 (92%) of 34 of patients undergoing FHTC and 36 (86%) of 42 of patients undergoing LHTC had at least one tube successfully cannulated. In total, 30 (78%) of 34 of patients undergoing FHTC and 32 (79%) of 42 patients undergoing LHTC had all occluded tubes successfully cannulated. Tubal perforation occurred in 1 (3%) of 34 FHTC cases and 3 (7%) of 42 LHTC cases. A similar percentage of non-IVF treatment-induced intrauterine pregnancies were achieved in the FHTC and LHTC groups (10/34 [29%] vs. 12/42 [29%]). Among patients who conceived without IVF, time from procedure to pregnancy was lower in the FHTC group (101 ± 124.6 days) compared with the LHTC group (228 ± 216 days). There was a significant difference in time to pregnancy when only those who conceived were considered (hazard ratio, 9.39; 95% confidence interval, 2.42-36.51); however, there was no significant difference when all subjects regardless of pregnancy outcome were analyzed (hazard ratio, 1.48; 95% confidence interval, 0.64-3.446). Conclusion: Fluoroscopically guided hysteroscopic tubal cannulation is a safe, effective, incision free procedure that results in comparable rates of tubal patency and intrauterine pregnancies as LHTC. This technique should be considered in women undergoing treatment of PTO when operative laparoscopy is not otherwise indicated.